1988
DOI: 10.1002/art.1780310107
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and joint count findings of the hand in rheumatoid arthritis. related and unrelated findings

Abstract: Radiographic and physical joint count findings of the hands and wrists of 148 patients with rheumatoid arthritis (RA) were analyzed in a cross‐sectional study. Quantitative radiographic scores for joint space narrowing, erosion, and malalignment were correlated highly with joint count scores for limitation of motion and deformity, and were correlated at considerably lower levels with joint swelling scores. Radiographic scores, however, were not correlated at all with joint count tenderness scores. That 2 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 21 publications
3
26
1
2
Order By: Relevance
“…The latter also reported more radiographic changes in the dominant hand which was not confirmed in the present study nor by Fuchs et al [24].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The latter also reported more radiographic changes in the dominant hand which was not confirmed in the present study nor by Fuchs et al [24].…”
Section: Discussioncontrasting
confidence: 60%
“…The modified index showed the same properties as the original one but in addition a significant correlation with the joint damage score was obtained. A connection between limitation of motion scores and radiographic findings has previously been observed [23,24].…”
Section: Discussionmentioning
confidence: 80%
“…Yelin, Meenan, and Nevitt in 1980 (14) indicated that demographic and functional measures were more significant than radiographic measures in determining work disability, a finding confirmed in our own studies (15). Although we regard radiographs as being of great value in monitoring disease and have studied radiographic progression extensively (8,(16)(17)(18)(19)(20)(21), functional status is a far more statistically and clinically significant predictor of work disability (15) …”
Section: To the Editorsupporting
confidence: 68%
“…Cross-sectional data from the baseline evaluation of these patients have been presented in previous reports concerning the joint count (50,51); radiographs (34,35,50,52,53); rheumatoid factor (35); grip strength, walk time, and button time (47); and self-report questionnaire data concerning ADL difficulty (36), pain (49), and helplessness (39,40). These reports include further details concerning methods used for data collection and data management.…”
Section: Patient Assessment At Baseline and 5-year Reviewmentioning
confidence: 99%